The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.11607/prd.3430
|View full text |Cite
|
Sign up to set email alerts
|

Color Compatibility of Gingival Shade Guides and Gingiva-Colored Dental Materials with Healthy Human Gingiva

Abstract: The CIELab and CIEDE2000 coverage error (ΔE* and ΔE', respectively) of basic shades of different gingival shade guides and gingiva-colored restorative dental materials (n = 5) was calculated as compared to a previously compiled database on healthy human gingiva. Data were analyzed using analysis of variance with Tukey-Kramer multiple-comparison test (P < .05). A 50:50% acceptability threshold of 4.6 for ΔE* and 4.1 for ΔE' was used to interpret the results. ΔE* / ΔE' ranged from 4.4/3.5 to 8.6/6.9. The majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 3 publications
1
31
0
Order By: Relevance
“…The same is true for a recent study that utilized the same database as this one. It reported that color distribution of several commercial gingival shade guides and corresponding materials (light‐curing composite, flourapatite glass ceramic, nano‐fluorapatite layering ceramic, and feldspar veneering ceramic) exhibited CEs well above AT: CE ab of shade guides ranged from 5.0 to 7.3, and from 4.4 to 8.6 for gingiva‐colored materials . This study proposed new gingival shade guide models, providing significant reductions of CE, falling below the AT in 4‐cluster models for both CIELAB and CIEDE2000.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The same is true for a recent study that utilized the same database as this one. It reported that color distribution of several commercial gingival shade guides and corresponding materials (light‐curing composite, flourapatite glass ceramic, nano‐fluorapatite layering ceramic, and feldspar veneering ceramic) exhibited CEs well above AT: CE ab of shade guides ranged from 5.0 to 7.3, and from 4.4 to 8.6 for gingiva‐colored materials . This study proposed new gingival shade guide models, providing significant reductions of CE, falling below the AT in 4‐cluster models for both CIELAB and CIEDE2000.…”
Section: Discussionsupporting
confidence: 52%
“…As CE varied depending the number of clusters/shade tabs (increasing the number of clusters provided lower CE and ME), the first null hypothesis of this study was rejected. The distribution of the gingival color points from the database is more harmonious and with relatively balanced frequency of tabs in 3–6 cluster models as compared with corresponding values for gingival shade guides and materials . These results were corroborated by the cross‐validation process.…”
Section: Discussionmentioning
confidence: 52%
“…For example, the coverage error (the mean of the best matches from one set of specimens to each sample of another set) above 1.8 (CIEDE2000) and 2.7 (CIELAB) can be interpreted through these sub‐categories of “unacceptability”. Although coverage error has been reported predominantly for comparisons between the existing dental shade guides and natural teeth and in computer modeling of shade guides, two recent papers reported on coverage error of gingiva‐colored dental materials to human gingiva . One of them reported that the coverage error for gingiva‐colored shade guides ranged from 3.6 to 5.3 (CIEDE2000) and from 5.0 to 7.3 (CIELAB), whereas corresponding values for gingiva‐colored dental materials were from 3.9 to 6.9 and from 4.4 to 8.6 (CIELAB) .…”
Section: Discussionmentioning
confidence: 99%
“…However, the color and esthetics of gingiva are far from irrelevant, drawing more attention of dental professionals and industry as the time passes by. Many restorative materials for gingiva are presently available, from resin composites and acrylics, through pink ceramic powders and milling products, to pink implants …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation